Odonata from Iberá Wetlands (Corrientes, Argentina): preliminary inventory and biodiversity - Muzon, Javier (2008)
A preliminary inventory of the Odonata from Iberá Wetlands and their area of influence (Corrientes, Argentina) is presented. Different kinds of environments were surveyed in seven localities. Seventy five species grouped in 33 genera and seven families were registered, from which three genera and 10 species are new records for the country. The localities belonging to the Iberá Wetland system show low endemicity and a high faunistic relationship with the Paraná basin.